Compact and non compact structures of the phi-four equation - İnç, Mustafa; Kilic, Bulent (Taylor & Francis Ltd, 2017)
In this paper, we establish exact special solutions of the phi-four equation. We use the reduction of order method and the He's variational principle for this equation. So, we get general formulae for the compacton, solitary pattern, soliton, and periodic solutions.
Keywords: Traveling-Wave Solutions; Nonlinear Evolution-Equations; Camassa-Holm; Physical Structures; Periodic-Solutions; Generalized Forms; Optical Solitons; Dispersion